Preliminary Data: an Adapted Hospital Elder Life Program to Prevent Delirium and Reduce Complications of Acute Illness in Long Term Care (HELP-LTC) delivered by Certified Nursing Assistants - Boockvar, Kenneth S. (J Am Geriatr Soc, 2016)
Nursing home (NH) patients have a high prevalence of delirium risk factors, experience 2-4 acute medical conditions (e.g., infections) each year, and have an incidence of delirium during these conditions that is similar to that of hospitalized older adults. Many NH patients with delirium do not return to their prior level of cognitive function. As compared to those without delirium, they are more likely to die, be hospitalized, and less likely to be discharged home. Research on the prevention or treatment of delirium in the NH remains limited. This article describes the development and pilot-testing of a multicomponent delirium prevention intervention in the NH setting adapted from the Hospital Elder Life Program (“HELP-LTC”). We developed delirium-risk reducing activities appropriate for functionally-impaired NH patients that were delivered during treatment for and recovery from acute illness, a novel patient targeting approach. Activities were provided by an expertly trained certified nursing assistant (CNA) who visited patients throughout the facility. We report on incident delirium, delirium remission, cognitive and physical function change, hospitalization, and death associated with acute medical conditions as ascertained by a program coordinator. We also report on the integration and acceptance of the CNAs’ activities by patients and staff. Hospitalization and death were ascertained in a non-intervention comparison group. Findings support a test of the intervention in a controlled trial. The potential impact is great: there are approximately 1.4 million NH patients in the U.S. and an estimated 1 million with dementia or cognitive impairment, a key delirium risk factor. An intervention would be broadly adoptable if the cost of the program’s CNAs were offset by a reduction in health care costs through prevention of hospitalization.